2012
DOI: 10.4082/kjfm.2012.33.5.262
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Efficacy and Safety of Non-steroidal Anti-inflammatory Drugs versus Acetaminophen in the Treatment of Episodic Tension-type Headache: A Meta-analysis of Randomized Placebo-controlled Trial Studies

Abstract: BackgroundNon-steroidal anti-inflammatory drugs (NSAIDs) and acetaminophen are widely used in the treatment of tension headache. The objective of this study was to evaluate and compare the efficacy and safety of single doses of acetaminophen and NSAIDs using meta-analysis of randomized placebo-controlled trial studies.MethodsWe searched MEDLINE, EMBASE, CINAHL, Cochrane, KMbase, KoreaMed, RiCH, National Assembly Library, Riss4u, and DBPIA for studies released through 27th July 2010. Two authors independently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, unlike NSAIDs, it does not cause gastric mucosal damage (Lanza et al, 1998;Yoon et al, 2012). Although the analgesic mechanism of APAP remains unclear and requires further elucidation, it is suggested that APAP may act centrally and be a weak inhibitor of PG synthesis (Anderson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike NSAIDs, it does not cause gastric mucosal damage (Lanza et al, 1998;Yoon et al, 2012). Although the analgesic mechanism of APAP remains unclear and requires further elucidation, it is suggested that APAP may act centrally and be a weak inhibitor of PG synthesis (Anderson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, high does NSAIDs could be relatively more effective for pain control 22). However, more adverse effects on the gastrointestinal system were reported in NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review (seven randomised controlled trials, 2421 participants) has shown that ibuprofen (an NSAID) is superior to paracetamol for pain associated with the surgical removal of wisdom teeth 31. Paracetamol appears to have similar efficacy to NSAIDs for the treatment of headache32 (systematic review of six randomised controlled trials, 2162 participants) and similar efficacy to NSAIDs and opioids for the treatment of renal colic (systematic review of 36 randomised controlled trials, 4887 participants) 33…”
Section: How Does Paracetamol Compare With Other Drugs For Common Paimentioning
confidence: 99%